Asprosin and meteorin-like protein immunoreactivity in invasive ductal breast carcinoma stages - Akkus, Gulsum; Koyuturk, Leyla Canpolat; Yilmaz, Mustafa; Hancer, Serhat; Ozercan, Ibrahim Hanifi; Kuloglu, Tuncay (Churchill Livingstone, 2022)
Aim: The study aimed to investigate asprosin (ASP) and meteorin-like (METRNL) protein immunoreactivity in invasive ductal breast cancer. Materials and methods: Overall, 60 cases of invasive ductal breast cancer (20 cases each of Grade 1, 2 and 3) were evaluated in addition to 20 normal breast tissues obtained from the Pathology Department Archive. ASP and METRNL expressions were assessed using immunohistochemical staining and visualised under a light microscope. Results: There was a significant difference in ASP and METRNL immunoreactivity among all the groups included in the study (p < 0.001). Cancer tissues with Grade 1, 2 and 3 showed a significant increase in ASP and METRNL immunoreactivity compared with the control group; however, no significant difference was noted among the cancer tissues with Grade 1, 2 and 3. Conclusions: ASP and METRNL immunoreactivity increased at the cellular level in invasive ductal breast cancer, but there was no difference in immunoreactivity among the breast cancer grades.
Keywords: Asprosin; Histopathology; Invasive ductal breast cancer; Meteorin-like protein